A Study on Stabilization of Subgrade by Using Recron Fibre Inmountainous Soil (International Journal of Innovative Research in Engineering & Management, 2022)
A series of proctor compaction and CBR  tests (un-soaked and soaked) are carried out on clayey soil,  mixed with various stabilizers (cement and Recron fiber) in  different percentages. Cement is mixed at the rate of 3%, 5%  and 7% by weight of dry soil, whereas Recron fiber (6mm)  are mixed at the rate of 0.3%, 0.5%, 1%, 2%, and 3% by  weight of dry soil. For better performance a combination of  different stabilizers in clayey soil (considering best dose of  individual) are also evaluate.
Keywords: Cement; Recron fiber; Subgrade; Soil; Transportation